KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Mahadi Kesuma Rambe; Rudianto Rudianto; Faisal Efendi Siregar; Amin Harahap (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The principal’s leadership plays an important and strategic role in improving the quality of education within educational institutions. The principal does not only carry out administrative functions but also acts as an instructional leader who is capable of directing, coordinating, and optimizing all school resources to achieve educational goals. However, various challenges related to the effectiveness of principal leadership in improving educational quality still exist, including managerial, pedagogical, and school culture development aspects. Therefore, this study aims to comprehensively examine the concepts, models, and contributions of principal leadership in improving educational quality through a literature review approach. This study employs a literature study method conducted through the exploration and analysis of various relevant written sources, including reference books, national and international journal articles, previous research findings, and educational policy documents. The research stages include literature search, selection of relevant sources, data classification, descriptive–qualitative analysis, and drawing conclusions. Based on the literature review, effective principal leadership can be identified through the ability to develop a clear vision, involve various stakeholders in decision-making processes, optimize the utilization of school resources, and build a positive and conducive school culture that supports the learning process. In addition, leadership models such as transformational, democratic, and instructional leadership have been proven to contribute positively to the improvement of educational quality. The findings of this study emphasize that the success of improving educational quality is strongly influenced by the quality of principal leadership; therefore, strengthening leadership competencies is an essential requirement in educational management. ABSTRAK Kepemimpinan kepala sekolah memegang peranan penting dan strategis dalam meningkatkan kualitas pendidikan di satuan pendidikan. Kepala sekolah tidak hanya menjalankan fungsi administratif, tetapi juga berperan sebagai pemimpin pembelajaran yang mampu mengarahkan, mengoordinasikan, serta mengoptimalkan seluruh sumber daya sekolah guna mencapai tujuan pendidikan. Namun, masih terdapat berbagai permasalahan terkait efektivitas kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan, baik dari aspek manajerial, pedagogis, maupun pengembangan budaya sekolah. Oleh karena itu, penelitian ini diarahkan untuk menelaah secara komprehensif konsep, model, serta kontribusi kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan melalui pendekatan kajian literatur. Penelitian ini menggunakan pendekatan studi literatur melalui penelusuran dan analisis berbagai sumber tertulis yang relevan, seperti buku referensi, artikel jurnal nasional dan internasional, hasil penelitian terdahulu, serta dokumen kebijakan pendidikan. Tahapan penelitian meliputi penelusuran literatur, seleksi sumber, pengelompokan data, analisis deskriptif-kualitatif, serta penarikan simpulan. Berdasarkan hasil telaah literatur, kepemimpinan kepala sekolah yang efektif ditunjukkan melalui kemampuan mengembangkan visi yang jelas, melibatkan berbagai pihak dalam pengambilan keputusan, mengoptimalkan pemanfaatan sumber daya sekolah, serta membangun budaya sekolah yang positif dan kondusif bagi proses pembelajaran. Selain itu, model kepemimpinan transformasional, demokratis, dan instruksional terbukti memberikan kontribusi positif terhadap peningkatan mutu pendidikan. Simpulan penelitian ini menegaskan bahwa peningkatan mutu pendidikan sangat dipengaruhi oleh kualitas kepemimpinan kepala sekolah sehingga penguatan kompetensi kepemimpinan menjadi kebutuhan penting dalam pengelolaan pendidikan.